1965
DOI: 10.1192/bjp.111.472.243
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Factors in Depressive Illness

Abstract: There seems to be a series of conceptual problems regarding depressive illness and its classification. First, there is the problem of whether these illnesses have some biological function, whether they represent attempts on the part of human organisms to deal with or escape from situations of stress, or whether they should be thought of simply as psychologically meaningless events. Eysenck (1960) and Wolpe (1958) make it clear that they regard neurotic symptoms as meaningless, maladaptive patterns which can an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
29
0
1

Year Published

1966
1966
2000
2000

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 135 publications
(32 citation statements)
references
References 14 publications
2
29
0
1
Order By: Relevance
“…Neurotic depressives also show lower AMS scores at the beginning and higher AMS scores at the end of inpatient treatment than endogenous depressives. According to discriminant analysis there is no significant difference neither in the number of life events nor in the biographic scale between neurotic and endogenous depressives, a result which is in accordance with Benjaminsen, 1981;Brown and Harris, 1978;Brown et al, 1979;Forrest et al, 1965;Leff et al, 1970;Paykel et al, 1969;Perris, 1984b;Thomson and Hendrie, 1972. Concerning the biographic scale in a strict sense our results are not correspondent to findings in the scientific literature. Parker (1979) found that neurotic depressives reported less parental care and greater maternal overprotection.…”
Section: Differences Between Neurotic and Endogenous Depressionsupporting
confidence: 68%
See 1 more Smart Citation
“…Neurotic depressives also show lower AMS scores at the beginning and higher AMS scores at the end of inpatient treatment than endogenous depressives. According to discriminant analysis there is no significant difference neither in the number of life events nor in the biographic scale between neurotic and endogenous depressives, a result which is in accordance with Benjaminsen, 1981;Brown and Harris, 1978;Brown et al, 1979;Forrest et al, 1965;Leff et al, 1970;Paykel et al, 1969;Perris, 1984b;Thomson and Hendrie, 1972. Concerning the biographic scale in a strict sense our results are not correspondent to findings in the scientific literature. Parker (1979) found that neurotic depressives reported less parental care and greater maternal overprotection.…”
Section: Differences Between Neurotic and Endogenous Depressionsupporting
confidence: 68%
“…Some authors found no difference between endogenous or rather psychotic depressive disorders and reactive or neurotic depressive disorders (Benjaminsen, 1981;Brown and Harris, 1978;Brown et al, 1979;Forrest et al, 1965;Leff et al, 1970;Nanko and Demura, 1993;Paykel et al, 1969;Perris, 1984b;Thomson and Hendrie, 1972). But there are also investigations which show a difference in life events between endogenous and reactive or rather neurotic depressive disorders.…”
mentioning
confidence: 99%
“…Most have attempted, with mixed success, to link loss of a parent during childhood with adult depression (28,29) and other forms of psychopathology (30,31). Overall, the literature is fairly consistent, however, that childhood parental loss in the absence of warm, quality caretaking is an important risk factor for the development of depression in adulthood (32-34).…”
Section: Introductionmentioning
confidence: 93%
“…All such events were not undcr the patient's control. In every compartment of RLE all events were enquired for and confirmation that events took place in the relevant period was obtained from relatives bearing in mind the tendency of depressed patients to recall events that 'explain' their mood (Brown and Harris 1978), to selective remembering of depressive events (Fava et al 1981) and to attribute depression to events which in fact resulted from the illness (Lewis 1938 andForrest et al 1965).…”
Section: Case Materials and Methodsmentioning
confidence: 99%